DOI: 10.6035/14031.2017.76657
|View full text |Cite
|
Sign up to set email alerts
|

Sinterización de compactos de vidrio y de composites vidrio-circón. Mecanismo y cinética del proceso

Abstract: Y para que conste a los efectos oportunos, firman el presente certificado en Catellón, a 25 de abril de 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…For every temperature, the results were fitted to straight lines from which the values of n S were obtained (Table 3). The average value of the Avrami parameter, , was consistent with the values obtained in the sintering of glass-zircon composites [14,31]. In those studies, it was verified that the JMAK model appropriately described the sintering process of these materials with values of n S that decreased from n = 0.7 for the glass, used as matrix, to n S ≈0.4, as the rigid particle (zircon) volume fraction increased and the ratio: rigid particle size/glass matrix size decreased.…”
Section: Kinetic Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…For every temperature, the results were fitted to straight lines from which the values of n S were obtained (Table 3). The average value of the Avrami parameter, , was consistent with the values obtained in the sintering of glass-zircon composites [14,31]. In those studies, it was verified that the JMAK model appropriately described the sintering process of these materials with values of n S that decreased from n = 0.7 for the glass, used as matrix, to n S ≈0.4, as the rigid particle (zircon) volume fraction increased and the ratio: rigid particle size/glass matrix size decreased.…”
Section: Kinetic Analysissupporting
confidence: 85%
“…In view of these results, the effect of temperature on the rate constant, k(T), was assumed to be due to the influence of this variable on the inverse of glass matrix viscosity, as reported elsewhere [14,31]. It can therefore be described by an expression, based on a VFT-type viscosity equation, of the form: (20) where B = 7100 K and T 0 =600 K are the values of the VFT equation parameters for viscosity of the glass matrix and A* is the pre-exponential factor.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…As the zircon volume fraction, f, increased, the sintering curves (Figure 4) obtained at a heating rate of 5K/min shifted towards higher temperatures, this effect increasing as zircon content rose. It was also observed that, at values of f≤0.43, the ρ versus T curves exhibited a sigmoidal shape and were satisfactorily fitted to the viscous flow sintering model developed by the present authors [4]. At higher zircon contents, the curves describing viscous flow sintering departed from the experimental values, thus indicating the occurrence of the zircon solution-reprecipitation mechanism.…”
Section: Composite Sintering Curvessupporting
confidence: 80%
“…where f max is the inclusion maximum packing fraction, which depends mainly on inclusion shape and size distribution amplitude, and n is a parameter that depends mainly on inclusion shape. For glass-zircon composites [4], glass-alumina composites [1], and complex glaze compositions [5], values have been obtained of 0.60≤f max ≤0.74 and n=4.5. On the other hand, various researchers [6] [7] [8] have attempted to analyse composite sintering rate, Śc, in the initial state of the process and composite effective viscosity, h c , using the percolation theory.…”
Section: Introductionmentioning
confidence: 99%
“…For glass-zircon composites [19], glass-alumina composites [20], and complex glaze compositions [21], values have been obtained of 74 . 0 60 .…”
Section:  (T) = Glass Viscosity (Pa·s)mentioning
confidence: 99%